Time Domain Similarity of Lightweight Parameters Based Soil Respiration Sensor Network Deployment. (15th June 2015) - Wang, Guoying; Mo, Lufeng; Zhao, Jizhong; Zhang, Chaoqi
Abstract : Deployment is a basic and key issue for all kinds of wireless sensor networks applications. Most of existing researches on deployment problem of wireless sensor network are on generic network level and not for specific application scenarios and also do not utilize any domain knowledge of practical applications. Focusing on the problem of limited number of sensing nodes in soil respiration sensor networks, using domain knowledge such as some lightweight parameters (temperature, humidity, etc.) influencing soil respiration and soil respiration having a day-periodic trend, we proposed a deployment method, TimSim, for soil respiration sensor network based on time domain similarity of lightweight parameters. Lightweight parameters data from positions in the region to be monitored are collected before the deployment of soil respiration sensing nodes, and then time domain similarities of lightweight data among different positions are analyzed, according to which these positions are divided into some groups. A representative position in each group is chosen to deploy a soil respiration sensing node. The experimental results show that TimSim method can place nodes to proper positions so as to monitor regional soil respiration carbon flux effectively with a smaller estimation error than uniform and random deployment methods.